Highly sensitive split ring resonator-based sensor for quality monitoring of edible oils - Muhammad Amir Khalil; Wong Hin Yong; Tehseen Batool; Ahasanul Hoque; Lo Yew Chiong; Hui Hwang Goh; Tonni Agustiono Kurniawan; Mohamed S. Soliman; Mohammad Tariqul Islam (Scientific Reports)
Abstract This research presents the design and analysis of a compact metamaterial (MTM)-based star-shaped split-ring resonator (SRR) enclosed in a square, constructed on a cost-effective substrate for liquid chemical sensing applications. The designed structure has dimensions of 10 × 10 mm2 and is optimized for detecting adulteration in edible oils. When the sample holder is filled with different percentages of oil samples, the resonance frequency of the MTM-based SRR sensor shift significantly. The measured results demonstrate that the proposed SRR sensor is superior in terms of sensitivity and quality factor compared to studies in the literature. The proposed sensor shows superior performance in sensitivity and quality factor (Q-factor) compared to existing sensors in the literature. It exhibits a remarkable sensitivity of 0.92 with a frequency shift of 760 MHz for adulteration detection, which is higher than sensors with shifts ranging from 140 to 600 MHz reported in previous studies. Additionally, the design has a high Q-factor of 149, indicating its efficiency in determining adulteration in edible oils. Additionally, the error rate in detecting adulteration is minimal at 3.1%, a significant improvement over prior sensors, which have error rates as high as 8%. These enhancements highlight the sensor’s potential in applications requiring precise, efficient, and cost-effective detection of edible oil adulteration, thus offering a significant advancement in both performance and practical utility over traditional methods.